Mathematics Learning Based on Lesson Study Using the Reciprocal Teaching Model in the Mathematical Statistics Course - Ahmad Yani T; Agus Winarji; Ilka Nur Awaliyah; Wahyu Anggraini; Meli Lestari (STKIP Singkawang, 2026)
This qualitative descriptive study aims to describe the implementation of mathematics learning based on Lesson Study using the Reciprocal Teaching model in the Mathematical Statistics course at FKIP Untan and ISBI Singkawang. The research focuses on improving students’ ability to write definitions and theorems symbolically through collaborative interactions among lecturers, students, and classroom contexts. The research procedure followed the Lesson Study cycle (plan–do–see), with data collected through interviews, observations, field notes, and assessments. Data were analyzed using the Miles and Huberman model, involving data reduction, presentation, and conclusion drawing. The results show that implementing Lesson Study with Reciprocal Teaching fosters dialogic, collaborative, and continuous learning. In the plan stage, collaborative planning produced a learning design incorporating the strategies of predicting, questioning, clarifying, and summarizing, aligned with students’ characteristics. The do stage revealed active student engagement in group discussions, SPSS practice, and symbolic writing of concepts, although some misconceptions regarding probability, distribution, and variance were still observed. The see stage provided a space for collaborative reflection to identify strengths—such as increased participation, mathematical communication, and conceptual understanding and weaknesses, including uneven participation and limited time allocation. The study concludes that integrating Lesson Study with the Reciprocal Teaching model effectively enhances students’ ability to write definitions and theorems symbolically while strengthening their understanding of Mathematical Statistics concepts. This model is recommended as an innovative strategy for preparing prospective teachers capable of managing reflective, interactive, and meaningful learning.Pembelajaran Matematika Berbasis Lesson Study Dengan Menggunakan Model Reciprocal Teaching Pada Mata Kuliah Statistika MatematikaABSTRAKPenelitian deskriptif kualitatif ini bertujuan untuk mendeskripsikan implementasi pembelajaran matematika berbasis Lesson Study dengan menggunakan model Reciprocal Teaching pada mata kuliah Statistika Matematika di FKIP Untan dan ISBI Singkawang. Fokus penelitian diarahkan pada peningkatan kemampuan mahasiswa dalam menuliskan definisi dan teorema secara simbolik melalui interaksi kolaboratif antara dosen, mahasiswa, dan konteks kelas. Prosedur penelitian mengikuti siklus Lesson Study (plan–do–see) dengan teknik pengumpulan data berupa wawancara, observasi, catatan lapangan, dan asesmen. Analisis data dilakukan dengan model Miles dan Huberman melalui reduksi, penyajian, serta penarikan kesimpulan. Hasil penelitian menunjukkan bahwa implementasi Lesson Study dengan Reciprocal Teaching mampu menciptakan pembelajaran yang dialogis, kolaboratif, dan berkesinambungan. Pada tahap plan, perencanaan kolaboratif menghasilkan rancangan pembelajaran dengan strategi predicting, questioning, clarifying, dan summarizing yang sesuai dengan karakteristik mahasiswa. Tahap do memperlihatkan keterlibatan aktif mahasiswa dalam diskusi kelompok, praktik penggunaan SPSS, dan penulisan konsep secara simbolik, meskipun masih ditemukan miskonsepsi terkait peluang, distribusi, dan variansi. Tahap see memberikan ruang refleksi kolaboratif untuk mengidentifikasi kelebihan berupa peningkatan partisipasi, komunikasi matematis, dan pemahaman konseptual, serta kelemahan berupa distribusi partisipasi yang belum merata dan keterbatasan waktu. Kesimpulan penelitian menegaskan bahwa integrasi Lesson Study dengan Reciprocal Teaching efektif meningkatkan kemampuan menulis definisi dan teorema dalam bentuk simbolik, sekaligus memperkuat pemahaman konsep Statistika Matematika. Model ini direkomendasikan sebagai strategi inovatif untuk menyiapkan calon guru yang mampu mengelola pembelajaran reflektif, interaktif, dan bermakna.Kata Kunci :Lesson Study; Model Reciprocal Teaching; Statistika Matematika